Implementation of the Principle of Facilitating Exercise of Shareholders' Rights under Polish Law: Critical Remarks - Mizerski, Dominik (Review of European and Comparative Law, 2026)
This article analyzes the impact of implementing EU Directive 2017/828 on strengthening shareholders rights and engagement in the Polish legal framework. Despite the directive's aim of facilitating the exercise of shareholders rights, its practical impact has been limited, with only minor improvements observed, such as the obligation for companies to confirm the receipt and registration of votes. The study uses the dogmatic and comparative methods to demonstrate that the legislative changes resulting from the implementation of Directive 2017/828 into Polish law have only marginally improved the legal position of shareholders of listed companies, whose shares are admitted to trading on a regulated market.